Do Turkish Nursing and Midwifery Students Teach Breast Self-Examination to Their Relatives? - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2010)
Aim: To describe health beliefs and breast self-examination (BSE) practice of Turkish female nursing and midwifery students and assess teaching of BSE to their mothers, sisters, relatives. Methods: The study was designed as a definition survey, withe data obtained from 113 participants, in third and fourth class and their mothers, sisters, relatives in Turkey. Data were collected by using a personal data form, knowledge evaluation form for BSE (Maurer 1997) and the Champion's Health Belief Model Scale. Results: Students had learned about breast cancer and BSE in their lessons one or two years previous to the study. Knowledge level scores of the students were 52.3 +/- 9.63 (min: 25, max: 75). Rate of regular BSE was 32.7%. When health belief scale assessed, the average susceptibility was 7.52 +/- 2.62, seriousness was 21.8 +/- 5.30, benefit was 16.7 +/- 4.45, barrier was 22.3 +/- 6.44, confidence was 40.3 +/- 6.67 and medical motivation was 26.6 +/- 4.22. A statistically significant difference in the rate of having regular BSE and benefit, barrier scores was noted (p<0.05). Regarding BSE training, 91.3% (n = 106) gave assistance to their mother and sisters, 42.6% (n = 48) to relatives, 6.2% (n = 7) to friends, and 5.4% (n = 6) to patients. Conclusions: Knowledge about breast cancer and BSE repetition training programs should be planned for nursing/midwifery students. Their susceptibility, belief and attitudes, medical motivation with BSE should thereby increase.
Keywords: Breast self examination; female nursing/midwifery students; training; family and friends; PEER EDUCATION MODEL; RELIABILITY; VALIDITY; BELIEFS; SCALE; WOMEN